KESEIMBANGAN ALAM SEKITAR DAN PEMBANGUNAN KOMUNITI JOHOR - Zainura Zainon Noor, editor, 603557; Siti Nur Hafizah Soid,editor 632746; 'Aaishah Radziah Jamaludin, contributor 632745; Fadhilah Yusof, contributor 560555; Rahmah Mohd. Lokoman, contributor 632744; Zulkifli Yusop, 1961-, contributor 493503; Mohd. Nadzri Md. Reba, contributor 615041; Lim, Leonard Yisheng, contributor 632743; Mohd. Rizaludin Mahmud, contributor 272101; Mohd. Fadhil Md. Din, contributor 283389; Norhidayah Md. Yunus, 1983-, contributor 633574; Shazwin Mat Taib, contributor 513808; et al. (Johor Bahru, Johor : PENERBIT UTM, 2021)
Includes bibliographical references and index.